Postoperative Pain Management among Registered Nurses in a Vietnamese Hospital - Phuong Hoang Vu; Duc Viet Tran; Yen Thi Le; Ha Thi Thu Do; Sao Thi Vu; Huong Thanh Dinh; Tu Huu Nguyen (The Scientific World Journal)
This study examined the postoperative pain management practices among registered nurses in an urban hospital in Vietnam. Data of 90 nurses about postoperative pain management practices and pain management at the department were collected. Results indicated that 83.3% of nurses reported that they regularly assessed the degree of pain for postoperative patients. Only 32.2% used assessment tools such as the numeric rating scale to measure pain. Experience in pain management and having guidelines in the department were associated with a higher score in pain management practice. Findings suggested that facilitating the use of pain instruments and developing pain management guidelines should be prioritized.